2009
DOI: 10.1177/1538574409344437
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Oxygenated Perfluorocarbons (PFCs) on Intestinal Ischemia Reperfusion Injury (I/R) in Rabbits

Abstract: Intraluminal administration of oxygenated PFCs seems that protect the intestine from the I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
0
18
4
Order By: Relevance
“…), whereas another study reported values of 4 · 05 ± 0 · 22, 6 · 80 ± 1 · 22, 5 · 67 ± 1 · 15 and 7 · 14 ± 0 · 58 mmol/L, higher than the concentrations in the present study (Ntinas et al. ). In one of these studies (Gunel et al.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…), whereas another study reported values of 4 · 05 ± 0 · 22, 6 · 80 ± 1 · 22, 5 · 67 ± 1 · 15 and 7 · 14 ± 0 · 58 mmol/L, higher than the concentrations in the present study (Ntinas et al. ). In one of these studies (Gunel et al.…”
Section: Discussioncontrasting
confidence: 90%
“…In another study, d ‐lactate concentrations measured using the lactate oxidase–peroxidase–chromogen sequence, another enzymatic technique, were higher than the values obtained in this study (Ntinas et al. ). However, only four rabbits were used, and sample size may have influenced the results obtained.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations